Aportaciones del psicología al desarrollo económico y social de los pueblo - Bustamante, J. A. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The author discusses economic and social development by making an enumerative summary of the most significant events that affect them.